Populism and Neopopulism in Latin America: Clientelism, Trade Union Organisation and Electoral Support in Mexico and Argentina in the 90s - Veronica Ronchi (Fondazione Eni Enrico Mattei (FEEM), 2007)
The state of anomie that has characterised and still characterises most Latin American countries, resulting from the fragmentation of the social fabric, has encouraged the rise of successful personalist leaderships in the 90s. This paper aims at investigating how neopopulism developed in Latin America, considering as main actors the two Presidents who have best embodied this ideal: Carlos Salinas de Gortari, (Mexico 1988-1994) and Carlos Menem (Argentina 1989-1999). Neopopulism is based on an economic project, the neoliberal policy based on cuts in the welfare, which seems very far from the populist positions of the past. Populism revives through the charisma of these Presidents, bypassing institutional or organisational forms of mediation between the leader and the masses. The development of selected social policies has gained strong political support from the lower classes, including extensive institutional reforms.
Keywords: I38; J88; N16; N26; N36; N46; 330; Latin America; Mexico; Argentina; 90s; Populism; Neopopulism; Politik; Wirtschaftsliberalismus; Gewerkschaft; Lateinamerika